2017
DOI: 10.1155/2017/4058124
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cognitive Rehabilitation Therapy on Poststroke Depression among Survivors of First Stroke Attack in Ibadan, Nigeria

Abstract: Background and Purpose Poststroke depression (PSD) is a common complication after stroke. There is no adequate treatment for PSD. This study examined efficacy of cognitive rehabilitation therapy (CRT) in the treatment of PSD among stroke survivors. Methods An experimental design, 30 participants with poststroke depression were randomly assigned into 3 groups of cognitive rehabilitation therapy (CRT), psychoeducation (PE), and the control group (CG). CRT consisted of nine sessions with three-phased sessions foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The sample size of the included studies is a variable that stands out in this systematic review. Excepting the clinical trial by Taravati et al [ 36 ] with n = 37, the clinical trial by Olukolade and Osinowo [ 40 ] with n = 30, and the one by Chun et al [ 42 ] with n = 59, the rest presented a sample size equal to or greater than 60 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size of the included studies is a variable that stands out in this systematic review. Excepting the clinical trial by Taravati et al [ 36 ] with n = 37, the clinical trial by Olukolade and Osinowo [ 40 ] with n = 30, and the one by Chun et al [ 42 ] with n = 59, the rest presented a sample size equal to or greater than 60 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Olukolade and Osinowo [ 40 ], Kongkasuwan et al [ 43 ] and Zhang et al [ 34 ], and Wang et al [ 38 ] highlighted the importance of diagnosing and treating post-stroke depression to improve the rehabilitation process and increasing patients’ quality of life, leading to a greater and more effective recovery.…”
Section: Discussionmentioning
confidence: 99%
“…If patients are diagnosed with PSD, they are usually treated with antidepressants ( 183 ). However, the effectiveness of antidepressants in clinical practice is only approximately 50% ( 184 ).…”
Section: Emotion-based Interventions In Treating Psdmentioning
confidence: 99%
“… 30 A prospective observational study in Nigeria also showed that, after nine sessions of CBT focused on activity stimulation, negative thoughts and people contacts, patients with PSD had better emotional well-being compared to controls. 31 Computerized CBT has also been explored in the past but did not prove superior over conventional CBT although only feasibility trials and studies with small population are available to date. 32 , 33 There is also an ongoing RCT on the use of an CBT-based iPAD application promoting self-reinforcement and positivity being performed among Japanese patients.…”
Section: Behavioral Therapymentioning
confidence: 99%